Effective pollination of ornitophylous flowers in a cloud forest of colombia - Martínez Meneses, Angie Lisseth; Torres-González, Alba Marina (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The plant-hummingbird interaction is fundamental for pollination in cloud forests. This research evaluated the effectiveness of pollination by hummingbirds in four species of plants in the Finca Zingara, Cali, Colombia. We assessed the hummingbird visits, the reproduction of the plants, the flowers’ energetic offer, and the deposition of pollen on the stigmas. We found that Guzmania multiflora was the most visited species by hummingbirds, followed by Cavendishia adenophora. In Columnea ferruginea and Columnea anisophylla we observed only four and one hermit hummingbird visits, respectively. The four species exhibit allogamy, Guzmania multiflora, and Cavendishia adenophora are auto compatible. Meanwhile, the two Columnea species are auto incompatible. The pollen that hummingbirds lay on the stigma is mainly legitime (Guzmania multiflora: 77,8% and Cavendishia adenophora: 51,6%). The higher volume of nectar accumulated during the day was produced by Guzmania multiflora: 28,53 µl and Cavendishia adenophora: 23,91 µl. The higher sucrose concentration in nectar was produced by Columnea ferruginea: 20,14% and Cavendishia adenophora: :17,4%. We conclude that hummingbirds are the effective pollinators of Guzmania multiflora and Cavendishia adenophora. Furthermore, for the hummingbirds in this study, it was more important to visit flowers of the species that produce the highest amount of nectar, than flowers of species with the highest sucrose concentration.